Actualization of historical knowledge in the Soviet popular science publications about China in the 1920–1930s - O.V. Telushkina (Ученые записки Казанского университета: Серия Гуманитарные науки)
After the October Revolution, increasing the level of adult education was recognized as one of the most important state tasks. Together with the “power”, the proletariat had to gain access to “knowledge”, or, at least, conversance of the political decisions taken by the party leadership. The need to convince the majority of the population that these decisions were the only correct and historically justified, led to an increase in the number of publications aimed to educate people and form a positive public opinion. The revolutionary upsurge in China was the reason for the revitalization of the activities of the USSR in this region, as well as the extreme interest of the Soviet citizens in this country. The publications analyzed in this paper, combining elements of scientific papers, journalism, and reports on the activities of political organizations, should satisfy this interest. Their texts included fragments of historical concepts, an analysis of the current political situation in China, and reflected the struggle that took place within the Soviet party elite.